2012
DOI: 10.1021/ma202388f
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of the Interphase Region of an Amphiphilic Polymer Conetwork Swollen in Polar and Nonpolar Solvent

Abstract: The most attractive property of amphiphilic polymer conetworks (APCNs) is their ability to swell in both polar and nonpolar solvents. Depending on the composition, their structure is phase separated on the nanometer scale possessing highly different morphologies. This special nanophase-separated structure provides numerous possible applications for heterogeneous chemical and biological processes. Although the interphase region can fundamentally influence the material transport between the different polarity ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
8
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…These novel polymeric systems belong to a rapidly emerging class of materials and have sparked enormous interest in the last few decades in both pure and applied sciences. 7,8,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] APCNs possess several unique characteristics, such as the amphiphilic swelling properties and the improved mechanical characteristics compared to homopolymer hydrogels. Moreover, a special property of these materials is their phase behaviour.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These novel polymeric systems belong to a rapidly emerging class of materials and have sparked enormous interest in the last few decades in both pure and applied sciences. 7,8,[16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] APCNs possess several unique characteristics, such as the amphiphilic swelling properties and the improved mechanical characteristics compared to homopolymer hydrogels. Moreover, a special property of these materials is their phase behaviour.…”
Section: Introductionmentioning
confidence: 99%
“…These domains have various proportions over the composition range and the phase separation in the APCNs leads to average domain sizes in the nanometer scale. Diversity of techniques involving differential scanning calorimetry (DSC), 22,30 small angle X-ray scattering (SAXS), 20,24,27 small angle neutron scattering (SANS), 25,27 transmission electron microscopy (TEM), 17,19,27,30 atomic force microscopy (AFM) 17,19,30,32 and solidstate NMR 20,21 were used to conrm the formation of separated nanodomains in these materials. The systematic study of the compositionally asymmetrical morphology of APCNs is of major importance, when a stable, bicontinuous nanophase-separated structure is formed over a broad composition window of both constituent phases with large inner surface between the distinct phases.…”
Section: Introductionmentioning
confidence: 99%
“…Besides, unlike homopolymer gels, CAPNs are able to swell in both polar and nonpolar solvents due to their amphiphilic nature, which is advantageous for use in both hydrophilic and hydrophobic drug delivery. 13 In this work, we developed an unprecedented type of amphiphilic, zwitterionic, and strong polymer network, i.e. PDMScrosslinked-NOCC amphiphilic polymer networks (PMSC CAPNs), by esterification between cross-linked PDMS diol [bis(hydroxyalkyl) terminated polydimethylsiloxane, silicone] and NOCC (N,O-carboxymethyl chitosan).…”
Section: Introductionmentioning
confidence: 99%
“…NMR studies with a focus on the interphase region of poly­( N , N -dimethylaminoethyl methacrylate)- l -polyisobutylene APCNs swollen in polar and nonpolar solvents were performed with deuterium solid-state NMR on conetworks with selectively deuterium labeled cross-linking molecules. It was shown that the mobility of the cross-link points, despite being polar, hardly changes when the network is swollen in water, but tremendously increases when swollen in n -heptane …”
mentioning
confidence: 99%